HUBUNGAN ANTARA USIA MENARCHE DAN LAMA MENSTRUASI DENGAN KEJADIAN DISMENORE PRIMER PADA REMAJA PUTRI DI SMK NEGERI 4 SURAKARTA - Gustina, Tina; , Anisa Catur Wijayanti, SKM., M.Epid; , Bejo Raharjo, SKM, M.Kes (2015)
Dysmenorrhea is a menstrual pain in the lower abdomen radiating to the waist and thighs, sometimes accompanied by nausea and vomiting, diarrhea, headache and emotional instability. This is because the substance prostaglandin. Prostaglandin is made by the inner lining of the uterus. Menstruation occurs before these substances increases and so menstruation occurs, decreases prostaglandin levels. The purpose of this study was to determine the relationship between age of menarche and old of menstrual with the incidence of primary dysmenorrhea in adolescent girls at SMK State 4 Surakarta. This study is observational analytic cross sectional. The population in this study was student of class X and XI as many as 714 students. Selection of the sample with proportional random sampling 148 students. Statistical test using Chi Square test. The results showed that there was no relationship between the age of menarche with the incidence of primary dysmenorrhea in adolescent girls at SMK Negeri 4 Surakarta (p=0,049), there was no relationship between the old of menstrual with the incidence of primary dysmenorrhea in adolescent girls at SMK Negeri 4 Surakarta (p = 0.783).